HUBUNGAN ANTARA PENGELUARAN UNTUK MINUM DAN POLA KONSUMSI AIR DENGAN STATUS HIDRASI PADA SISWI SMP UNGGULAN BINA INSANI SURABAYA - Yuvienta Ernovitania; Sri Sumarmi (Universitas Airlangga, 2017)
Currently many teenagers only drinking when they are thirsty, while the thirst is a sign of dehydration. Moreover they have another habit, they didn’t allocate their money for buying drink and they also didn’t bring a tumblr at school. That unhealthy habit can lead dehydration. One of the dehydration’s impact was fatigue and lost of focus. The purpose of this research was to analyze the relationship between d rink’s expense and water consumption patterns with the h ydration status at SMP Unggulan Bina Insani Surabaya. This study was an observational study with cross sectional design using simple random sampling technique. The sample was 50 students. The variables were drink’s expense, water consumption patterns, and hydration status. This study was conducted at SMP Unggulan Bina Insani Surabaya. Data analysis using spearman/pearson and chi-square test with α = 0.05. The result of this study showed that most of the student had average drink’s expense, less water consumption patterns, and Minimal Dehydration. There was a relationship between d rink’s expense (p = 0.047), and d rinking pattern (p = 0.000) with h ydration status. The conclusion of this study was the two independent variables such d rink’s expense and water consumption patterns show a significant relationship with h ydration status at SMP Unggulan Bina Insani Surabaya. Suggestions for the school was to provide counseling about the definition, signs, impact, and how to prevent dehydration in students in order to avoid the incidence of dehydration.